Propuesta de Estaciones de Aprendizaje para concienciar sobre emisiones de CO2 y ODS en Educación Secundaria y Universitaria - Rosser Limiñana, Pablo; Soler Ortiz, Seila; Ortiz-Cermeño, Eva (Octaedro, 2024)
The educational project “Learning Stations for Awareness of CO2 Emissions and SDGs in the Classroom” aims to raise awareness among students about CO2 emissions and Sustainable Development Goals (SDGs) through a didactic approach based on five different Learning Stations: reading, dialogue, STEM, geography, and advertising design. At each station, students will carry out activities related to CO2 emissions and their impact on the environment, as well as the SDGs linked to this problem. The project promotes active and participatory learning, allowing students to develop critical and creative skills to address a complex and relevant problem for our society. At the end of each station, a test will be conducted to verify if the students have acquired the necessary knowledge and skills, and a rubric has been designed to evaluate their performance in each activity. It is expected that this project will contribute to the formation of a more responsible and committed citizenship with the environment, willing to take concrete measures to reduce CO2 emissions and build a more sustainable future.
Keywords: Learning Stations; CO2 emissions; SDGs; awareness; environmental education